P141 IBUS-SAS for Crohn's disease ultrasound activity: initial validation and research of the optimal cut-off score. (27th May 2021) - Dragoni, G; Innocenti, T; Lynch, E N; Fiorini, C; Parisio, L; Roselli, J; Bagnoli, S; Macrì, G; Rogai, F; Milani, S; Galli, A; Milla, M
Abstract: Background: Intestinal ultrasound (IUS) is being widely accepted as a reliable tool to objectively monitor Crohn's disease (CD) activity. Recently, an international panel of experts developed an IUS score, called IBUS-SAS (International Bowel Ultrasound Segmental Activity Score). Our aim was to validate this index in a real-life cohort and find a cut-off score that correlates with common lab results of intestinal inflammation. Methods: All CD patients referred to our unit for IUS examination between November 2020 and February 2021 were scored with the IBUS-SAS. Clinical activity at the time of presentation using Harvey-Bradshaw Index (HBI) was recorded, with remission defined as HBI<5. Faecal calprotectin (FC) and C-reactive protein (CRP) within 8 weeks from IUS were also included. Upper limits of normal for CRP and FC were set at 0.5 mg/dL and 150 µg/g, respectively. Combined biomarkers remission (CBR) was defined as both negative CRP and FC. Pearson's correlation (rho = ρ) was performed between IBUS-SAS and the other parameters. ROC analyses were carried out to find a predictive cut-off value of IBUS-SAS for CBR. Results: In total, 40 CD patients were included. The characteristics of the cohort are reported in Table 1 . In patients in clinical remission, IBUS-SAS was 27.52±17.42 (mean ±SD); in patients with clinical activity, it was 59.23±22.36. In individuals with negative FC, IBUS-SAS mean value was 26.59±16.85; in case of FC >150 µg/g, it was 50.13±22.16. IBUS-SAS score directly correlated with all parameters considered: clinical activity (ρ=0.38, P=0.01), CRP (ρ=0.33, P=0.04) and FC (ρ=0.42, P=0.007). ROC analysis of IBUS-SAS for CBR revealed an area under the curve of 0.92 (95% CI 0.86–0.97), with a sensitivity of 83.3% and a specificity of 91.3% for a cut-off value of 42.9. Conclusion: This pilot analysis of IBUS-SAS confirmed its potential to precisely define CD activity, correlating both with clinical scores and biomarkers. An IBUS-SAS cut-off value of 42.9 has demonstrated the highest sensitivity and specificity in predicting normal values of both CRP and FC. A comparison of IBUS-SAS with endoscopic activity and a larger cohort are needed to confirm these findings.